Cytosolic factor- and TOM-independent import of C-tail-anchored mitochondrial outer membrane proteins - Setoguchi, Kiyoko (Nature Publishing Group, 2006)
C-tail-anchored (C-TA) proteins are anchored to specific organelle membranes by a single transmembrane segment (TMS) at the C-terminus, extruding the N-terminal functional domains into the cytoplasm in which the TMS and following basic segment function as the membrane-targeting signals. Here, we analyzed the import route of mitochondrial outer membrane (MOM) C-TA proteins, Bak, Bcl-XL, and Omp25, using digitonin-permeabilized HeLa cells, which provide specific and efficient import under competitive conditions. These experiments revealed that (i) C-TA proteins were imported to the MOM through a common pathway independent of the components of the preprotein translocase of the outer membrane, (ii) the C-TA protein-targeting signal functioned autonomously in the absence of cytoplasmic factors that specifically recognize the targeting signals and deliver the preproteins to the MOM, (iii) the function of a cytoplasmic chaperone was required if the cytoplasmic domains of the C-TA proteins assumed an import-incompetent conformation, and intriguingly, (iv) the MOM-targeting signal of Bak, in the context of the Bak molecule, required activation by the interaction of its cytoplasmic domain with VDAC2 before MOM targeting.